IMPLEMENTATION OF THE RIGHT TO EDUCATION AND UTILISATION OF SCIENCE, TECHNOLOGY, ARTS AND CULTURE BASED ON ARTICLE 28C PARAGRAPH (1) OF THE 1945 CONSTITUTION - Hernita; Gunawan Widjaja (International Journal of Teaching and Learning, 2025)
This study discusses the implementation of the right to education and the utilisation of science, technology, arts, and culture based on Article 28C paragraph (1) of the 1945 Constitution, which guarantees every citizen the right to develop themselves to improve their quality of life. Education is considered a fundamental right that must be provided by the state, but reality shows that there are still gaps in access, quality, and equity of educational services between urban and rural areas, rich and poor groups, and majority and minority groups. Similarly, the right to utilise science, technology, arts, and culture has not been optimally realised due to a lack of research support, low digital literacy, weak protection of intellectual property, and the challenges of globalisation that have the potential to erode local cultural identities. The research method used is a normative juridical approach combined with a conceptual approach. Data was obtained from primary, secondary, and tertiary legal materials, which were then analysed descriptively and analytically. The results of the study show that despite various regulations and government programmes, the implementation of Article 28C paragraph (1) still experiences a gap between normative principles and empirical reality. The fulfilment of these rights requires strengthening access to and equity in education, support for research and innovation, technological literacy, cultural protection, and political commitment to holistic human development. In conclusion, the implementation of Article 28C paragraph (1) of the 1945 Constitution in Indonesia still faces structural, cultural, and technical obstacles in ensuring that all citizens can benefit from education, science, technology, arts, and culture. Therefore, synergy between the state, society, and the private sector is key to optimising these constitutional rights for the sake of national welfare and competitiveness.